2012
DOI: 10.3177/jnsv.58.240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Intake Levels of Dietary Protein and Physical Exercise on Bone Mineral Density and Bone Strength in Growing Male Rats

Abstract: Summary Having higher bone mineral density (BMD) during growth is complexly infl uenced by many factors. For example, nutrition and physical exercise are key factors. However, few studies have investigated the combined effects of these factors. In this study, we investigated the effect of physical exercise and different levels of protein intake on BMD and bone strength of growing male rats. Forty-seven male Wistar rats (5 wk old) were randomized into 10% (Low), 20% (Moderate) and 40% (High) protein diet groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
2
16
1
2
Order By: Relevance
“…On the other hand, exercise caused a minor, but significant, downregulation of bone mineral apposition (e.g., MAR) and sizerelated measurements. Similar findings have been reported for other nutritional manipulation studies (e.g., CR and PR) (14)(15)(16) as well as endurance interventions (16,22). Because BW is known to be associated with bone size, we further conducted a PearsonÕs correlation between BW and various size-related indices.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…On the other hand, exercise caused a minor, but significant, downregulation of bone mineral apposition (e.g., MAR) and sizerelated measurements. Similar findings have been reported for other nutritional manipulation studies (e.g., CR and PR) (14)(15)(16) as well as endurance interventions (16,22). Because BW is known to be associated with bone size, we further conducted a PearsonÕs correlation between BW and various size-related indices.…”
Section: Discussionsupporting
confidence: 62%
“…Endurance athletes (e.g., long-distance runners) have normal or subnormal levels of bone mineral density (BMD) and bone mineral content (BMC) (20,21). Similar observations were drawn from animal studies showing that endurance training of growing or adult male rats was associated with a reduction or no change in bone size, mineral accumulation, and extrinsic bone strength (16,22,23). However, when normalized to body mass, healthy endurance athletes and endurance-trained animals had normal or higher BMD or BMC compared with nonexercise control groups (24,25).…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…Protein deficiency could decrease the secretion of insulin-like growth factor 1 (IGF-1) [13], which may prevent normal growth of bone mass. Recently, we also demonstrated that a low protein intake suppressed the acquisition of bone mass and the increase of bone strength during growth period [14]. Conversely, a high protein intake results in higher urinary calcium (Ca) excretion, which may lead to accelerated bone resorption [15].…”
Section: Introductionmentioning
confidence: 99%